Effectiveness of tailored talks between a cancer screening specialist and general practitioners to improve the uptake of colorectal cancer screening in Ancona (Italy) during the pandemic period - Cecilia Acuti Martellucci; Giusi Giacomini; Maria Elena Flacco; Lamberto Manzoli; Margherita Morettini; Mosè Martellucci; Sara Rosati; Silvia Bizzarri; Matthew Palmer; Lidia Pascucci; Marco Uncini; Francesca Pasqualini (European Journal of General Practice)
Background Colorectal cancer (CRC) screening uptake in many countries has been low and further impacted by the COVID-19 pandemic. General Practitioners (GPs) are key facilitators, however research on their impact on organised CRC screening is still limited.Objectives To evaluate the effectiveness of tailored talks with GPs to increase population uptake of the long-established CRC screening programme in Ancona province, Italy.Methods In this prospective cohort study, one-to-one tailored talks were organised in January 2020 between the GPs of one county of the province (with GPs from other counties as controls) and the screening programme physician-in-chief to discuss the deployment and effectiveness of organised screening. Data was extracted from the National Healthcare System datasets and linear regression was used to assess the potential predictors of CRC screening uptake.Results The mean CRC screening uptake remained stable from 39.9% in 2018–19 to 40.8% in 2020–21 in the 22 GPs of the intervention county, whereas it statistically significantly decreased from 38.7% to 34.7% in the 232 control GPs. In multivariate analyses, belonging to the intervention county was associated with an improved uptake compared to the control counties (+5.1%; 95% Confidence Intervals – CI: 2.0%; 8.1%).Conclusion Persons cared for by GPs who received a tailored talk with a cancer screening specialist avoided a drop in CRC screening adherence, which characterised all other Italian screening programmes during the COVID-19 emergency. If future randomised trials confirm the impact of tailored talks, they may be incorporated into existing strategies to improve population CRC screening uptake.